The Works of Ibn Wāḍiḥ Al-Yaqūbī (Volume 3) : An English Translation. - Gordon, Matthew S. (Islamic History and Civilization, 2018)
The Works of Ibn Wāḍiḥ al-Yaʿqūbī , a three volume set, contains a fully annotated translation of the extant writings of Abū al-ʿAbbās al-Yaʿqūbī, a Muslim imperial official and polymath of the third/ninth century, along with an introduction to these works and a biographical sketch of their author. The most important of the works are the History ( Ta'rikh ) and his Geography ( Kitab al-buldan ). It also contains a new translation of al-Yaʿqūbī's political essay ( Mushakalat al-nas ) and a set of fragmentary texts drawn from other Arabic medieval works. Al-Yaʿqūbī's writings are among the earliest surviving Arabic-language works of the Islamic period, and thus offer an invaluable body of evidence on patterns of early Islamic history, social and economic organization, and cultural production. Contributors: Laila Asser, Paul Cobb, Lawrence I. Conrad, Elton Daniel, Fred Donner, Michael Fishbein, Matthew S. Gordon, Sidney H. Griffith, Wadad Kadi (al-Qāḍī), Lutz Richter-Bernberg, Chase F. Robinson, Everett K. Rowson The hardback edition of this title is also available as part of a 3-volume set (hardback, ISBN 978-90-04-35608-5), click here .